Role of Fiberoptic Bronchoscopy in the Rapid Diagnosis of Sputum Smear-negative Disseminated Tuberculosis with Pulmonary Miliary Infiltrates - Khan, Fahmi Yousef (Oman Med J, 2020)
OBJECTIVES: We sought to evaluate the role of bronchoscopy-related procedures such as bronchoalveolar lavage (BAL), bronchial wash (BW), bronchial brush (B brush), transbronchial biopsy (TBB), and post-bronchoscopy sputum (PBS), alone or in combination, in the rapid diagnosis of negative sputum smear disseminated tuberculosis (TB). METHODS: We performed a secondary post hoc analysis of data collected from our previous study entitled "Disseminated tuberculosis among adult patients admitted to Hamad General Hospital, Qatar: A five-year hospital-based study" with a modified objective. RESULTS: We identified 27 patients. BAL fluid was positive for acid-fast bacilli (AFB) smear in 7/27 (25.9%) patients and were culture-positive for Myobacterium tuberculosis in 17/27 (63.0%) cases, while BW collections were smear-positive in 9/27 (33.3%) cases and culture-positive for M. tuberculosis in 18/27 (66.7%) cases. TBB showed caseating granulomas in 10/16 (62.5%) cases and one case of non-caseating granuloma (6.3%). PBS was positive for AFB in 4/8 (50.0%) patients. The combination of these procedures enabled us to diagnose disseminated TB rapidly in 22 (81.5%) cases. CONCLUSIONS: Bronchoscopy proved to be an effective method for the rapid diagnosis of disseminated TB in patients in whom sputum smear microscopy was negative.